Proceedings of the 14th International Conference on World Wide Web - WWW '05 2005
DOI: 10.1145/1060745.1060831
|View full text |Cite
|
Sign up to set email alerts
|

Information search and re-access strategies of experienced web users

Abstract: Experienced web users have strategies for information search and re-access that are not directly supported by web browsers or search engines. We studied how prevalent these strategies are and whether even experienced users have problems with searching and re-accessing information. With this aim, we conducted a survey with 236 experienced web users. The results showed that this group has frequently used key strategies (e.g., using several browser windows in parallel) that they find important, whereas some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
168
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(194 citation statements)
references
References 27 publications
(35 reference statements)
13
168
1
5
Order By: Relevance
“…Use of log data is common in IR studies but is limited when establishing context in the use of the search facility [1]. Therefore, in this study we take a mixed methods approach [5], utilising recorded observation to gather a rich data set of user searching strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Use of log data is common in IR studies but is limited when establishing context in the use of the search facility [1]. Therefore, in this study we take a mixed methods approach [5], utilising recorded observation to gather a rich data set of user searching strategies.…”
Section: Methodsmentioning
confidence: 99%
“…Expert searchers also use more synonyms (Hsieh-Yee, 1993;Vakkari, 2001); however, there is no consensus about their use of complex search expressions involving truncations, Boolean operators and phrase searching. Holscher and Strube (2000) and Chu and Law (2007a) found greater use of Booleans, but Aula (2005) and Hsieh-Yee, (1993) found fewer Boolean queries being used by experts. This has been seen as evidence either that expert searchers can construct more complex queries, or that they are able to select exactly the right term to gain useful results.…”
Section: Studies Of Expertisementioning
confidence: 97%
“…Not surprisingly, these have found that experts have much more complex information seeking strategies. They will persist for longer with searches, use more varied strategies and more diverse sources, use both browsing and searching, and reformulate queries if an initial search does not produce useful results (Holscher & Strube, 2000;Hsieh-Yee, 1993;Aula et al 2005;Cothey, 2002). Good knowledge of the subject domain is also vital (Vakkari, 2002;Kuhlthau, 2004).…”
Section: Studies Of Expertisementioning
confidence: 99%
“…The importance of a tool for visualizing, analyzing and comparing parallel browser behavior is further highlighted in [4], since users tend to use multiple windows and tabs as means for backtracking (e.g., users abandon the use of in-browser back operations in favor of opening new tabs and switching between them) and multitasking (e.g., users interact with one tab while Web pages are being loaded and processed in others). Similarly, findings from [22,27] suggest that users often employ parallel browsing in Web search tasks for reasons like comparing search results, executing multiple queries, interacting with a page while others are being loaded, etc.…”
Section: Related Researchmentioning
confidence: 99%